Judgment in managerial decision making - Bazerman, Max H. (New York : John Wiley and Sons, 1998)
This book is about: Introduction to managerial decision making; Biases; Judgment under uncertainty; The nonrational escalation of commitment; Fairness in decision making; ...
Keywords: Business; Management; Decision making; Management; Decision making